Impact of financing models and carbon allowance allocation rules in a supply chain. (15th June 2021) - Wang, Minxue; Zhao, Ruidong; Li, Bo
Abstract: This paper focuses on a capital-constrained supply chain system under a carbon trading environment. Bank Credit Financing and Trade Credit Financing models are designed under the grandfathering and benchmarking allocation rules. Through constructing a Stackelberg game model consisting of a supplier and a capital-constrained manufacturer who is investing in carbon emission reduction, we analyze the optimal decisions and financing selection strategies under different allowance allocation rules. These results show that the manufacturer always invests a higher carbon emission reduction under the benchmarking rule. Meanwhile, he always prefers BCF no matter how the carbon allocation rules change. Whereas, the upstream supplier would like to provide delayed payment under TCF. The government is beneficial to provide the benchmarking rule to the manufacturer when his historical carbon emission is lower, otherwise, the government can implement the grandfathering rule.